2011
DOI: 10.1159/000320453
|View full text |Cite
|
Sign up to set email alerts
|

Role of DNA Methylation in the Development of Diffuse-Type Gastric Cancer

Abstract: Cancer cells exhibit two opposing methylation abnormalities: genome-wide hypomethylation and gene promoter hypermethylation. Downregulation of E-cadherin (CDH1) plays a key role in the development of diffuse-type gastric cancer, and DNA methylation is a major cause of the gene’s silencing. Hereditary diffuse gastric cancer is caused by germline mutation of CDH1 gene, and DNA methylation frequently serves as the second hit completely inactivating the gene. In sporadic diffuse-type gastric cancer, methylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 135 publications
2
45
0
2
Order By: Relevance
“…Etiologic analysis has shown that individuals with H. pylorirelated gastritis, severe atrophy, and intestinal metaplasia are at high risk of developing intestinal type gastric cancers, which are often associated with metachronous gastric cancer development. On the other hand, individuals with H. pylori-related pangastritis and enlarged-fold gastritis, which are lesions without mucosal atrophy or intestinal metaplasia, are at increased risk of developing diffuse type gastric cancers (3). Surveillance of these high-risk patients using reliable and accurate predictive markers is important for reducing the incidence of gastric cancer and its mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Etiologic analysis has shown that individuals with H. pylorirelated gastritis, severe atrophy, and intestinal metaplasia are at high risk of developing intestinal type gastric cancers, which are often associated with metachronous gastric cancer development. On the other hand, individuals with H. pylori-related pangastritis and enlarged-fold gastritis, which are lesions without mucosal atrophy or intestinal metaplasia, are at increased risk of developing diffuse type gastric cancers (3). Surveillance of these high-risk patients using reliable and accurate predictive markers is important for reducing the incidence of gastric cancer and its mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The list of genes aberrantly methylated in gastric cancer is growing and now includes genes involved in cell-cycle regulation, apoptosis, immune function, cell signaling, and tumor invasion and metastasis (3,5). In addition, aberrant DNA methylation is frequently observed in noncancerous gastric mucosa in H. pylori-infected patients, suggesting aberrant DNA methylation is an early step during gastric carcinogenesis (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…This leads to abnormal morphogenesis and architecture of epithelial tissue, loss of cellular polarity and contact inhibition, unregulated growth, and invasion of adjacent tissue. 12,13 Approximately 50 distinct CDH1 mutations throughout the gene have been described. 2,11,13 In addition to mutations, DNA methylation of the CDH1 promoter has been observed and may completely deactivate the gene, decreasing expression of E-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Approximately 50 distinct CDH1 mutations throughout the gene have been described. 2,11,13 In addition to mutations, DNA methylation of the CDH1 promoter has been observed and may completely deactivate the gene, decreasing expression of E-cadherin. 13 Another recent observation is that when E-cadherin expression is greatly decreased or absent, exon v6-containing CD44 isoforms are over-expressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation